(untitled) (Journal of Pakistan Orthopaedic Association, 2014)
Shaft of radius may be exposed surgically by dorsal (Thompson)or volar (Henry) approaches. Both of these approaches are adopted depending upon the operative requirement or expertise of the surgeon. However, both of these approaches have their advantages and disadvantages. The author felt the need of any other approach, which did not have disadvantages of both approaches and at the same time have advantages of both approaches. The goal of this study was to determine the validity of a novel, direct lateral or radial approach to the shaft of radius throughout its full length. We hypothesized that by this approach, complications of both the standard Henry and Thompson approaches may be avoided. A descriptive case series was conducted in the department of orthopedic surgery, King Edward Medical College for this purpose. From October 2012 to April 2014. Twenty-seven patients were operated for internal fixation of fracture of radius with dynamic compression plate. Fracture was exposed through lateral approach and internally fixed by standard AO principles. Patients were followed up on 4th, 8th and 12th postoperative week and functional outcome was assessed. No patient included in the study had posterior interosseous nerve palsy, hematoma formation or restriction of supination or pronation by the end of the final follow up period. Absence of any complication related to the standard volar and dorsal approaches indicated the validity of this approach. Comparison with the other approaches is needed to determine its advantage over others. MESH words: Lateral Approach, Shaft Radius